Analisis Pengaruh Teknologi Informasi dan Komunikasi, Indeks Pembangunan Manusia, Jumlah Penduduk, dan Tingkat Partisipasi Angkatan Kerja terhadap Ketimpangan Pendapatan di Indonesia Tahun 2019-2023 - Agus Hananto Wibowo; Aisyah, Siti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Income inequality remains a crucial issue in the development process in Indonesia, although various strategies and policies have been implemented to reduce it. This study evaluates the role of information and communication technology (ICT) in influencing income inequality in Indonesia during the period 2019 to 2023. The control variables used in this study include the Human Development Index (HDI), population, and labor force participation rate (TPAK). The method applied is panel data regression. The findings show that increasing access to and utilization of ICT, as well as increasing HDI, have a positive impact on reducing income inequality. Conversely, a large population and low labor force participation tend to exacerbate inequality. Based on these results, this study recommends improving the quality of the workforce through skills training, as well as equalizing access to ICT. This study contributes to scientific studies that link technological developments with the dynamics of income inequality.